Extracellular bacterial synthesis of protein-functionalized ferromagnetic Co3O4 nanocrystals and imaging of self-organization of bacterial cells under stress after exposure to metal ions - Kumar, Umesh; Shete, Ashvini; Harle, Arti S.; Kasyutich, Oksana; Schwarzacher, W.; Pundle, Archana; Poddar, Pankaj (Chemistry of Materials, 2008)
Co3O4, which crystallizes in the spinet phase at temperatures much higher than ambient temperatures, orders antiferromagnetically below its Neel temperature (similar to 40 K). However, in nanosize, it shows ferromagnetic ordering due to surface canting, disorder, imperfect oxygen atom coordination, etc. Here, for the first time, we report the synthesis of single-crystalline, ferromagnetic Co3O4 nanoparticles functionalized with proteins (size 5-7 nm) using cobalt acetate as precursor at room temperature in aqueous medium by a metal-tolerant marine bacterium isolated from the coast of the Arabian Sea. Energetically unfavorable change in the oxidation state of Co atoms from (+2 to +3) during synthesis by the bacterial strain was evidenced by X-ray photoelectron spectroscopy. The effect on the morphology of bacterial cells after exposure to the cobalt acetate was imaged by scanning electron microscopy showing cooperative, self-organized. structured colony formation, possibly due to the interbacterial communication under external stress.

Effect of cultural conditions and media constituents on production of penicillin V acylase and CTAB treatment to enhance whole-cell enzyme activity of rhodotorula aurantiaca (NCIM 3425) - Kumar, Atul; Singh, Sanjay; Poddar, Pankaj; Prabhune, Asmita; Pundle, Archana (Applied Biochemistry and Biotechnology, 2009)
Penicillin V acylase (PVA) is a pharmaceutically important enzyme as it plays a vital role in the manufacture of semi-synthetic beta-lactam antibiotics. Rhodotorula aurantiaca (NCIM 3425) produced high levels of intracellular penicillin V acylase after 18 h at pH 8.0 and temperature 27 degrees C. Fructose was the best carbon source for PVA production, whereas tryptone was the best nitrogen source to produce the enzyme up to 170 and 1,088 IU/l of culture, respectively. Additionally, the cell-bound PVA activity was enhanced on treatment with cationic detergent. Whole-cell activity was found to be doubled (204%) on treatment of 0.01 g dry weight of cells with 50 mu g/ml solution of N-cetyl-N,N,N-trimethylammoniumbromide at pH 8.0 for 1 h at room temperature. Atomic force microscopy images of permeabilized cells show perturbation in the cell wall and offer first-ever visual illustration of surface structure modifications that occur during permeabilization of R. aurantiaca cells leading to enhancement in activity of intracellular enzyme.
Keywords: Atomic force microscopy; Intracellular enzyme; Penicillin Vacylase; Permeabilization; Rhodotorula aurantiaca

Effect of organic solvents on cell-bound penicillin V acylase activity of erwinia aroideae (DSMZ 30186): a permeabilization effect - Kumar, Atul; Pundle, Archana (Journal of Molecular Catalysis B-Enzymatic, 2009)
Erwinia aroideae (DSMZ 30186) is a potential microbial culture to produce intracellular penicillin V acylase (PVA). The whole cell PVA activity was improved by permeabilization with various organic solvents. The cell-bound PVA activity showed an eightfold increase upon treatment with chloroform (5 mu L/mg(dry) (biomass)) for 10 min and diethyl ether (10 mu L/mg(dry) (biomass)) for 45 min. Hexane, toluene, ethyl acetate and dichloromethane enhanced the enzyme activity up to two-, six-, four- and two-fold, respectively; whereas, PVA activity declined drastically on permeabilization with acetone, pyridine and alcohols. The physicochemical properties of the organic solvents used for permeabilization were correlated with the change in activity. It was found that solvents with high hydrophobicity (log P > 0.68) and lower dielectric constant (< 9) were relatively effective in increasing PVA activity. These results allow systematic selection of suitable solvent for best performance. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: dielectric constant; Erwinia aroideae; Hydrophobicity; Organic solvents; Penicillin V acylase; Permeabilization